2004
DOI: 10.1080/02813430410006693
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas arising from implementation of the European guidelines on cardiovascular disease prevention in clinical practice A descriptive epidemiological study

Abstract: Implementation of the 2003 European guidelines on CVD prevention would label a large majority of Norwegian adults as having unfavourably high cholesterol and/or blood pressure levels. The current biomedical standards appear to invalidate demographic health statistics. The theoretical basis on which the guidelines rest should thereby be scrutinized with regard to scientific methodology and consistency. Important ethical dilemmas arise at the point of guideline implementation, relating to risk labelling and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 16 publications
2
54
0
7
Order By: Relevance
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
“…The gap between observed and guideline-recommended LLD use may reflect the fact that adherence to Framingham-based thresholds for intervention has been problematic in clinical practice. Norwegian population studies have shown that European SCORE-based guidelines classify most adults at high CVD risk with an ''unfavourable'' high cholesterol [2,5,6]. Implementation of these guidelines may lead to a marked increase in pharmacological treatment, especially in men and among the elderly [5].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the 2003 European guidelines on cardiovascular disease prevention [9] could imply that 76% of Norwegians 20 years and older and 90% of Norwegians 50 years and older should be told that they have unfavourably high cholesterol and/or blood pressure levels [10]. From these figures, it is evident that fundamentally new and unrecognized dilemmas emerge once we consider the aggregated implications of these individually based recommendations.…”
Section: Editorialmentioning
confidence: 95%
“…From these figures, it is evident that fundamentally new and unrecognized dilemmas emerge once we consider the aggregated implications of these individually based recommendations. This means that preventive medicine may be facing a major moral challenge [10]. The USA, Iceland, and Norway are currently numbers 1, 4, and 5 on the OECD ranking list of national healthcare expenditure in the world (OECD Health Data 2004).…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations